PENINGKATAN KEMAMPUAN BERBISNIS DIGITAL BAGI SISWA SMA/MA DI KOTA TASIKMLAYA - Kusnandar, Deasy Lestary; Bintari, Vivi Indah; Sari, Dewi Permata; Mufreni, Alfin Nur Fahmi; Saputra, Yuyus (ABDI MAKARTI, 2024)
Current technological advances cannot be separated from people's lives. Current developments in technology and science also encourage the field of management science to continue to make improvements in terms of productivity, creativity and effectiveness. Digital transformation has changed the business world so much that something called digital business has emerged. Digital business is a type of service business that utilizes sophisticated technology when creating a product or marketing it. The aim to be achieved in this service is to increase SMA/MA students' insight into digital business and make it easier for them to carry out low-fund based businesses that are effective and efficient in accordance with the needs of teenagers and even adults who want to start a business. The methods used in this service activity are socialization/counseling, training, discussions, simulations and application of digital business. With this service activity, the expected result is that SMA/MA students will have an understanding of the importance of entrepreneurship by utilizing technology so that interest in digital entrepreneurship among Madrasah Aliyah students in Tasikmalaya City will increase. This service activity contributes to schools or madrasas in equipping their graduates to have digital business skills so they can produce young digital entrepreneurs.